Effect of Hormonal Therapy for Volume Reduction, Lower Urinary Tract Symptom Relief and Voiding Symptoms in Prostate Cancer: Leuprolide vs Goserelin - Yikilmaz, Taha Numan; Ozturk, Erdem; Hizli, Fatih; Hamidi, Nurullah; Basar, Halil (Urology Journal, 2019)
Aim. The complaints of lower urinary tract symptoms (LUTS) in cases with Prostate carcinoma (Pca) depend on coexisting benign prostate hyperplasia (BPH) or aging bladder. We aimed to investigate and compare the effect of goserelin acetate with leuprolide acetate on total prostate volume (TPV), post voiding residue (PVR), International Prostate Symptom Score (IPSS) and maximum flow rate (Qmax) reduction on cases of advanced Pca. Methods. Patients with advanced Pca were treated with goserelin acetate (10.8 mg/3 months) or leuprolide acetate (22.5 mg/3 months) for 6 months. Changes in Prostate specific antigen (PSA), testesterone level, TPV, IPSS, PVR, and Qmax were assessed every 3 months. Results. Fifty-one patients analyzed in this study. Mean percent decrease in PSA and testesterone from baseline to 6th month was not significantly difference between two groups (respectively; p = 0.9, p = 0.15) but TPV was reduced by -20.2 % ± 4.8 and -15.6 % ± 1.04, the median total IPSS score was decreased by -34.77 % ± 8.8 and -19.77 % ± 6.1, median Qmax increased by 45.34 % ± 10.16 and 23.21 % ± 6.93, median PVR decreased by -31.54 % ± 8.4 and -19.23 % ± 5.5, respectively for two groups (all parameters (p < 0.05)) Conclusion. In this study, we observed that the improvement of voiding parameters goserelin acetate was beter than leuprolide acetate. Especially it was detected the superiority of goserelin acetate group on the reduction of TPV, PVR and IPSS. Oncological outcomes were not different in both groups.